Changes in Shaping the Open Data Performance Expectancy for Information Society Development Strategies in Europe - Iwona ZDONEK; Anna SOŁTYSIK-PIORUNKIEWICZ (Communications of International Proceedings, 2021)
The main purpose of the paper is to describe the changes in shaping open data performance expectancy for information society in Europe, esp. in context of European strategy for data development. There are three objectives of the paper: 1) finding the currently dominant sectors in open data performance expectancy creation; (2) finding the growth rate of open data-based products or services; (3) finding the geographical areas of Europe for each sector. The research methods are based on analysis of data dynamics and data visualization. The analyzed data come from texts promoting digital products and services that use open data. The research covers 427 digital products and services based on open data. The time frame covers the period from January 2018 to January 2021 and the research focuses mainly on European issues. The research results show that the Transport sector uses open data the most. The second place in the ranking is taken by Education, Culture & Sport sector and the third one by Government & Public.
Keywords: European information society; open data performance expectancy; visualization; dynamics analysis